Factors Influencing Students' Preferences to Pursue International Advanced Pharmacy Practice Experiences - Trisha Seys Ranola; Amanda Margolis; Connie Kraus (University of Minnesota Libraries Publishing, 2018)
The Problem: To improve the quality of the international APPE program and facilitate growth, a questionnaire was developed to identify perceived barriers for selection of and ways to increase interest in international APPEs. Survey Design: A questionnaire was administered to two consecutive third-year classes to gauge interest, perceived barriers and possible facilitators for engagement in international APPEs. Key Findings:  Cost and need to travel independently were most frequently identified as barriers to participating in international APPEs.  Suggestions to increase participation in international APPEs include: schools of pharmacy actively developing funding support, pairing students for international APPEs, and earlier targeted marketing. Disclosures: None Type: Note